LITERATURE REVIEW : FAKTOR TERJADINYA UNSAFE ACTION PADA PEKERJA SEKTOR MANUFAKTUR - Dwi Ayu Desmayanny; Ida Wahyuni; Ekawati Ekawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2020)
According to H.W.Heinrich, 88% of occupational accidents are caused by unsafe actions, 10% are caused by unsafe conditions and 2% are caused by other factors. Unsafe actions are human failure in following the instructions and work procedures that caused work accidents. This study aimed to analyze the relation between work fatigue, supervisors, and co-workers with unsafe actions in manufacturing sector workers. The method used in this research was a literature study, conducted online through several trusted websites or internet sites such as JSTOR, SpringerLink, Scopus, ScienceDirect, EBSCOhost, Cambridge core, Emeraldinsight, and Google Scholar. The research was conducted on 16 articles consisting of 11 national articles and five international articles. The results of the research conducted on workers in the manufacturing sector showed that four out of the five articles showed there was a relation between work fatigue and unsafe actions, work fatigue could cause a decreased alertness, concentration, and motivation so that workers tend to do unsafe actions. Eight out of the nine articles showed the relation between supervision and unsafe actions, supervision could foster compliance and awareness of the importance of occupational safety and health for themselves, other workers, and the work environment. Three out of the four articles showed there was a relation between co-workers and unsafe actions because co-workers could be a role model for other workers in taking action while they’re working.